Transformational Leadership di Kantor Pelayanan Desa - Deberina Syurfi Yunina; Wahyu Eko Pujianto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to explore and analyze the application of transformational leadership in Village Service Offices. Through a qualitative approach with a case study method, data was collected through in-depth interviews with Village Heads and their staff, field observations, and analysis of related documents. The research results show that the characteristics of transformational leadership, such as Idealized Influence, Intellectual Stimulation, Individualized Consideration and Inspirational Motivation have created an inspiring and inclusive work environment. The Damarsi Village Head actively motivates village officials and the community to contribute optimally in realizing the village development vision. Positive impacts are also seen in the active participation of team members in decision making, increased creativity and innovation, and development of individual skills. However, several challenges and areas for improvement were also identified.